2021
DOI: 10.33003/fjs-2020-0404-510
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Calibration Approach for Ratio Estimator in Stratified Sampling

Abstract: Calibration is a technique for the adjustment of the original design weight to improve the precision of the survey. There is a dearth of information on calibration approach adapted for survey such that the survey cost is put into consideration.  This research work developed a modified calibration approach for improving survey precision by considering the cost function. Data set on vegetable and tobacco productions (metric tonnes) were considered for this study. The data were obtained from the website of Food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Only then can he make the best choice for the patient. As one of the most significant data mining research techniques, the association rule is helpful in this situation [19][20][21][22][23][24][25]. In census data, association rule mining has a lot of potential.…”
Section: A Association Rule Mining In Various Areasmentioning
confidence: 99%
“…Only then can he make the best choice for the patient. As one of the most significant data mining research techniques, the association rule is helpful in this situation [19][20][21][22][23][24][25]. In census data, association rule mining has a lot of potential.…”
Section: A Association Rule Mining In Various Areasmentioning
confidence: 99%
“…Amab 42 proposed the optimum estimation of a finite population total in PPS sampling with a replacement for multicharacter surveys. Olayiwolla et al 43 suggested the PPS method to enhance the efficiency of the estimator in two-stage sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Amab 42 proposed the optimum estimation of a finite population total in PPS sampling with a replacement for multicharacter surveys. Olayiwolla et al 43 suggested the PPS method to enhance the efficiency of the estimator in two-stage sampling. In this article, the primary aim of the current work is to propose a new improved generalized class of estimators for the estimation of finite population mean using two auxiliary variables under PPS. The bias and mean squared error (MSE) of the proposed estimator is derived up to the first order of approximation. Through use of the real data sets from various domains and a simulation study, the application of the proposed estimator is highlighted. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation